Will the future BE POSITIVE? Early life experience as a signal to the developing brain pre school entry. (3rd July 2019) - Rifkin-Graboi, Anne; Khng, Kiat Hui; Cheung, Pierina; Tsotsi, Stella; Sun, He; Kwok, Fuyu; Yu, Yue; Xie, Huichao; Yang, Yang; Chen, Mo; Ng, Chee Chin; Hu, Pei Lin; et al.
ABSTRACT: We suggest that prior to school entry, our earliest "teachers" and "learning settings" —that is, our parents, caregivers, and homes—provide signals about our environmental conditions. In turn, our brains may interpret this information as cues indicating the types of environments we will likely face and adapt accordingly. We discuss ways in which two such early-life cues—bilingual exposure and sensitive caregiving quality, influence "domain general" neurocircuitry and associated functioning (e.g., temperament and emotional reactivity, emotion regulation, relational memory, exploratory play, and executive functioning), as well as pre-academic outcomes. We conclude by discussing the need for early upstream intervention programmes, as well as the need for additional research including our upcoming "BE POSITIVE" study, designed to help bridge the gap between the community, home, and school environments.